Effects of maternal protein restriction during pregnancy and lactation on milk composition and offspring development. Issue 2 (26th July 2019) - Bautista, C. J.; Bautista, R. J.; Montaño, S.; Reyes-Castro, L. A.; Rodriguez-Peña, O. N.; Ibáñez, C. A.; Nathanielsz, P.W.; Zambrano, E.
Abstract: Before weaning, breast milk is the physiological form of neonatal nutrition, providing pups with all nutrient requirements. Maternal low-protein diet (LPD) during pregnancy and lactation induces adverse changes in key maternal organs, which have negative effects on pup development. We studied the effects of maternal LPD on liver weight, mammary gland (MG) cell differentiation, milk composition and production and pup development throughout lactation. We fed rats with control (C) or LPD (R) during pregnancy and lactation. At 7 d early, 14 d mid and 21 d late lactation stages, maternal biochemical parameters, body, liver and MG weights were analysed. MG cell differentiation was analysed by haematoxylin and eosin staining; milk nutrient composition and production were studied; pup body, liver and brain weights, hippocampal arachidonic acid (AA) and DHA were quantified. Results showed lower body and liver weights, minor MG cell differentiation and lower serum insulin and TAG in R compared with C. R milk contained less protein and higher AA at early and mid stages compared with C. R pup milk and fat intake were lower at all stages. R protein intake at early and mid stages and DHA intake at mid and late stages were lower compared with C. In R pups, lower body, liver and brain weights were associated with decreased hippocampal AA and DHA. We conclude that maternal LPD impairs liver and MG function and induces significant changes in maternal milk composition, pup milk intake and organ development.